Predictive Factors for Recurrence of Papillary Thyroid Carcinoma in Children and Adolescents - Gui, Yan; Huang, Dongmei; Hou, Yun; Wei, Xudong; Zhang, Jinming; Wang, Junyi (Frontiers in Oncology, 2022)
Background. The incidence of papillary thyroid carcinoma (PTC) in children and adolescents has increasing, but the data of long-term outcome are limited. There are few literatures on the clinicopathological characteristics and prognosis of PTC in children and adolescents in China. Therefore, it is necessary to identify clinicopathological features to precisely predict clinical prognosis and to help choose the optimal method and perform the best therapeutic regimen. Methods. This study was a retrospective analysis of patients undergoing thyroidectomy at Tianjin Medical University Cancer Institute and Hospital. We analyzed the factors related to the clinicopathological features and prognosis of PTC in children and adolescents. Results. 95 juvenile PTC patients who underwent thyroidectomy were enrolled. Our research found that patients in younger age (﹤14 years) were predominantly multifocality, positive preoperative Tg, higher recurrence rate and the number of lymph node metastases (LNM) was more than the older group (14-18 years). Maximal tumor size﹥2cm, T stage and multifocality were the risk factors for LNM and the number of LNM (P﹤0.05). Multivariate analysis displayed the number of central LNM was the independent risk factors for lateral LNM, and multifocality was the independent risk factors for the number of central and lateral LNM. The younger age at diagnosis, positive preoperative TSH, maximal tumor size﹥2cm, lateral LNM, number of LNM, N staging and ATA pediatric risk were related to poor prognosis in PTC patients (P﹤0.05). Cox regression analysis found the younger age at diagnose, positive preoperative TSH were independent risk factors for recurrence of PTC in children and adolescents. Conclusions. Our study showed that the clinicopathological characteristics of the younger age were highly aggressive, prone to metastases and higher recurrence rate than the older age. In our opinion, patients with the following characteristics such as the younger age at diagnose, positive preoperative TSH, maximal tumor size﹥2cm, lateral LNM and the number of LNM﹥5, may be considered for more aggressive treatments, prophylactic or therapeutic dissection of additional metastatic LNs to prevent and reduce the recurrence rate.